A scoping approach to systematically review published reviews: Adaptations and recommendations. (22nd November 2017) - Schultz, Annette; Goertzen, Leah; Rothney, Janet; Wener, Pamela; Enns, Jennifer; Halas, Gayle; Katz, Alan
Abstract : Knowledge translation is a central focus of the health research community, which includes strategies to synthesize published research to support uptake within health care practice and policy arenas. Within the literature concerning review methodologies, a new discussion has emerged concerning methods that review and synthesize published review articles. In this paper, our multidisciplinary team from family medicine, nursing, dental hygiene, kinesiology, occupational therapy, physiology, population health, clinical psychology, and library sciences contributes to this discussion by sharing our experiences in conducting 3 scoping reviews of published review studies. A brief discussion of Cochrane Collaboration overview reviews and Joanna Briggs Institute umbrella reviews foreshadows a discussion of insights from our experiences of conducting the 3 scoping reviews of published reviews. We address 6 adaptations along with our recommendations for each, which may guide other researchers with designing scoping review approaches to synthesize published reviews. The ability of researchers to publish research findings is growing, and our ability to effectively transfer findings into useful evidence for health care practice and policy is imperative to our work.